If it's not what You are looking for type in the equation solver your own equation and let us solve it.
.5x+1.5x=x+4.5-.5x
We simplify the equation to the form, which is simple to understand
.5x+1.5x=x+4.5-.5x
We move all terms containing x to the left and all other terms to the right.
+ 0.5x+1.5x-1x + 0.5x=+4.5
We simplify left and right side of the equation.
+1.5x=+4.5
We divide both sides of the equation by 1.5 to get x.
x=3
| 3(.70)=(w+3)(42) | | (13b-5)-6(2b+2)=-6 | | -13+2=5(1+4) | | 2x^2+148x-1680=0 | | 14-(5m+4)=3+3m-17 | | -10=-n-4n | | 4t=3t-8 | | 14-5m+4=3+3m-17 | | 4-8=-5(1-u) | | 36x^2-42x+49=0 | | x+3=4x-33 | | 8x+8+5=-19 | | -6x^2=-7x-8 | | 2d+7=d-7 | | 0.055(x+4000)=0.08+0.04(2000) | | 4a^2-52a+144=0 | | 5+6x=x+65 | | 5x+41-6x=1-7x+4 | | 56.08+57.98= | | 96=+4(6x-6) | | 2-5r+2r^2=0 | | 2x^2+6+2x=0 | | 32c+3=15+26c | | 10y-7y-7=47.57 | | 0.6x-0.3(3)=4.5 | | X^3-2x^2-19x+20=5 | | U+7=11 | | q^2+2q=-1 | | 3x^2+49+77=0 | | 8(w-7)=5w-29 | | 3x-5(3-x)=7x+21-5+x | | 5x+6=4(x-2) |